2011
DOI: 10.1002/cctc.201100375
|View full text |Cite
|
Sign up to set email alerts
|

para‐Selective Aerobic Oxidative CH Olefination of Aminobenzenes Catalyzed by Palladium/Molybdovanadophosphoric acid/2,4,6‐Trimethylbenzoic Acid System

Abstract: Pick of the bunch: Oxidative CH olefination of aminobenzenes with acrylates was achieved using a palladium/molybdovanadophosphoric acid (HPMoV)/2,4,6‐trimethylbenzoic acid (TMBA) system under O2 (1 atm) in DMF. The highly regio‐ and stereoselective CH olefination of basic substrates such as aminobenzenes is important in organic synthesis; (E)‐para‐alkenyl‐substituted aminobenzenes were produced in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…With regard to the Pd catalyst used in this reaction, PdCl 2 (PhCN) 2 gave the best result (90% yield), whereas the use of Pd(OAc) 2 and Pd(acac) 2 , which showed high activities in our previously reported Pd(II)/HPMoV/O 2 [44][45][46][47][48][49][50][51][52] and Pd(II)/NPMoV/O 2 [53][54][55][56] catalytic systems, gave only 7-14% of the desired products 3. Catalyst possessing less acidic counter ion such as PdCl 2 (PhCN) 2 is preferable to avoid over-coordination of the aniline nitrogen to Pd center.…”
Section: Oxidative Amination Of Electron-deficient Alkenes With Seconmentioning
confidence: 87%
See 1 more Smart Citation
“…With regard to the Pd catalyst used in this reaction, PdCl 2 (PhCN) 2 gave the best result (90% yield), whereas the use of Pd(OAc) 2 and Pd(acac) 2 , which showed high activities in our previously reported Pd(II)/HPMoV/O 2 [44][45][46][47][48][49][50][51][52] and Pd(II)/NPMoV/O 2 [53][54][55][56] catalytic systems, gave only 7-14% of the desired products 3. Catalyst possessing less acidic counter ion such as PdCl 2 (PhCN) 2 is preferable to avoid over-coordination of the aniline nitrogen to Pd center.…”
Section: Oxidative Amination Of Electron-deficient Alkenes With Seconmentioning
confidence: 87%
“…Our group showed that the Pd(II)/HPMoV/O 2 system was an efficient catalyst for the oxidative alkenylation of coupling reactions of arenes (known as the direct Mizoroki-Heck reaction) through direct aromatic or alkenyl C-H bond activation [47][48][49][50][51]. In addition, we recently reported that the oxidative C-H alkenylation of aminobenzenes was achieved using a Pd/HPMoV/2,4,6-trimethylbenzoic acid catalytic system [52].…”
Section: Open Accessmentioning
confidence: 99%
“…The best‐known example of a Pd(II)/POMs/O 2 ‐catalyzed reaction is the Wacker‐type oxidation of ethylene to acetaldehyde, which is also applicable to other olefins 12. Recently, Ishii and Obora developed the oxidative coupling of benzene with α,β‐unsaturated aldehydes,13 acrylates,14 ethylene15 and acrylonitrile16 by the Pd(II)/HPMo 11 V/O 2 system under acidic conditions and Obora has reported CH olefination of aminobenzenes catalyzed by the Pd(II)/HPMo 11 V/O 2 system 17…”
Section: Screens For Direct Ch Olefination Of Indole 1a With N‐butylmentioning
confidence: 99%
“…[2] Generally, primary and secondary anilines can be conveniently substituted to install various directing groups (e.g., the NH-or N-substituted urea and amide, phosphoramidate, 2-pyridylsulfonyl, 2-pyridyl, N-nitroso, and methanesulfonamide groups) for aromatic C À H functionalization at the proximal site. [6] However, the transition-metal-catalyzed C À H activation of tertiary anilines remains less developed except for few examples on para-selective transformations [7] and the recently reported oxidative ortho CÀH alkenylation/N-dealkylative carbonylation of tertiary anilines (tertiary amines probably act as a directing group). [4,5] In addition, the N,N-dimethylaminomethyl group has been disclosed as a directing group for both oxidative Heck and arylation reactions.…”
mentioning
confidence: 99%
“…[4,5] In addition, the N,N-dimethylaminomethyl group has been disclosed as a directing group for both oxidative Heck and arylation reactions. [6] However, the transition-metal-catalyzed C À H activation of tertiary anilines remains less developed except for few examples on para-selective transformations [7] and the recently reported oxidative ortho CÀH alkenylation/N-dealkylative carbonylation of tertiary anilines (tertiary amines probably act as a directing group). [8] Therefore, it is highly valuable to develop CÀH activation for the synthesis of ortho-functionalized tertiary anilines.…”
mentioning
confidence: 99%